Service life estimation of electric vehicle lithium-ion battery pack using arrhenius mathematical model - Rammohan, A.; Wang, Yong; Kannappan S, Subbu; Kumar P, Suresh; Ashok, Bragadeshwaran; Kotb, Hossam; AboRas, Kareem M.; Yousef, Amr (Frontiers in Energy Research, 2024)
Durability is a desired characteristic for all battery packs in Electric Vehicles. In this study, the service life of the EV battery pack under real-world operating conditions is projected using an Arrhenius mathematical simulation model. The model comprises a 39.2 kWh EV Lithium-Ion battery pack integrated with a three-phase inverter to convert the battery pack's Direct Current output to Alternating Current. In addition, the Alternating Current output is coupled to a 100 kW permanent magnet synchronous motor, which is regarded as the load. A field-oriented controller provides pulse width-modulated output signals that are supplied back to the inverter to generate the correct driving current. Variable conditions of charge rate (C-rate: 1.25C -4C), discharge rate (C-rate: 0.5C -4C), temperature (25°C -60°C), and depth of discharge (30% -90%) are evaluated to determine the battery pack's service life. Under a 4C charge rate/0.5C discharge rate and 50% depth of discharge, the modeling results indicate the battery pack has a service life of approximately 6,000 hours at low temperatures (25°C) and roughly 3,000 hours at high temperatures (60°C). The model has been validated by comparing the results with experimental data from the literature.